HUBUNGAN AKTIFITAS FISIK DENGAN KENAIKAN BERAT BADAN PADA AKSEPTOR KB GESTIN F2 DI PUSKESMAS PURWOYOSO SEMARANG - Nurhanifah, Tia; Maharani, Kristina (Ensiklopedia of Journal, 2026)
Combined injection birth control can be an option for all women of reproductive age with poor adherence. Most acceptors often complain that after two months of injectable birth control, they feel they have gained weight. Many have switched to other birth control methods because of weight gain. This study aimed to determine the relationship between physical activity and weight gain in Gestin F2 contraceptive acceptors at the Purwoyoso Health Center, Semarang. This type of research is a quantitative study with a cross-sectional approach. The population in this study was 45 people who were in the working area of Purwoyoso Health Center in Semarang. The sampling technique used total  sampling and obtained a total of 45 respondents. Data collection was carried out using a questionnaire. Data analysis was carried out using univariate analysis with the presentation of data in the form of a frequency distribution and bivariate analysis with Chi-square (p-value <0.05). The results showed that physical activity had a p-value of 0.040. Therefore, it could be concluded that physical activity Physical activity is related to weight gain in respondents who are Gestin F2 KB acceptors at the Purwoyoso Health Center, Semarang with a p-value > 0.04. Keywords:  Aktifitas Fisik, Gestin F2, KB Suntik 2 Bulan, kenaikan berat badan